Moniezia benedeni infection promoting ICOS+ T cell proliferation in sheep (Ovis aries) small intestine - Baoshan Wang; Wanling Yao; LiLan Zhang; Lidong Jiang; Jing Pan; Wenzhu Chai; Zhen Huang; Sihan Zuo; Zhenpeng Li; Yanming Wei; Wangdong Zhang (BMC Veterinary Research)
Abstract Background Cellular immunity mechanisms play a crucial role in regulating anti-parasite immunity. ICOS is one of the core factors of multitype T cell subsets involved in the regulation of immune homeostasis. The aim of this experiment was to investigate the distribution patterns of ICOS+ T cells in the small intestine of sheep and determine the impact of Moniezia benedeni (M. benedeni) infection on these cells. Methods In this study, a sheep pET-28a-ICOS recombinant plasmid was constructed, and the recombinant protein was obtained through induced expression in BL21 (DE3) cells. Furthermore, a rabbit polyclonal antibody against sheep ICOS was produced. The expression of ICOS in the sheep small intestine was analyzed using immunofluorescence and ELISA, comparing the results before and after M. benedeni infection. Results The findings revealed that the purified recombinant ICOS protein had the anticipated size (14.2 kDa). The rabbit anti-sheep ICOS polyclonal antibody showed good specificity and a titer of 1:128,000. ELISA results indicated a significant increase in ICOS expression in all segments of the small intestine after M. benedeni infection (P < 0.05). The ileum exhibited the most substantial increase in expression (P < 0.001), followed by the jejunum (P < 0.05) and duodenum (P < 0.05). Immunofluorescence analysis demonstrated that ICOS+ T cells are diffusely distributed in the intestinal epithelium and around the intestinal glands in the lamina propria of the duodenum, jejunum, and ileum of sheep. Moreover, after being infected with M. benedeni, the number of ICOS+ T cells in all intestinal segments significantly increases (P < 0.05), with the most significant increase in the intestinal epithelium of the duodenum. Conclusions These findings suggest that M. benedeni infection in sheep can stimulate the proliferation of ICOS+ T cells in the small intestine. This lays the foundation for future research on the role of ICOS+ T cells in regulating cellular immunity against parasitic infections in different segments of the small intestine. Graphical Abstract